solve: -6 (5c + 4) - 3 = -2

So we have to use the distributive property first, and distribute the number into the parenthesis.

So, we multiply -6, the outside number, by every inside term: -6*5c + -6*4 -3 = -2

This simplifies to -30c-24-3=-2, or -30c-27=-2

We add both sides by 27: -30c=25

We then divide both sides by -30, making c=-25/30=-5/6

So, assuming you are solving for c, the answer would actually be c = -5/6.

Hope this helps!

Secure Information

Content will be erased after question is completed.

Enter the email address associated with your account, and we will email you a link to reset your password.

Forgot your password?

Sign Up